Observer based output feedback tuning for underwater remotely operated vehicle based on linear quadratic performance - Mohd Aras, Mohd Shahrieel; Abdullah, Shahrum Shah; Kamarudin, Muhammad Nizam; Abdul Rahman, Ahmad Fadzli Nizam; Abdul Azis, Fadilah; Jaafar, Hazriq Izzuan (AIP Publishing, 2015)
This paper describes the effectiveness of observer-based output feedback for Unmanned Underwater Vehicle (UUV) with Linear Quadratic Regulation (LQR) performance. Tuning of observer parameters is crucial for tracking purpose. Prior to tuning facility, the ranges of observer and LQR parameters are obtained via system output cum error. The validation of this technique using unmanned underwater vehicles called Remotely Operated Vehicle (ROV) modelling helps to improve steady state performance of system response. The ROV modeling is focused for depth control using ROV 1 developed by the Underwater Technology Research Group (UTeRG). The results are showing that this technique improves steady state performances in term of overshoot and settling time of the system response.